Вы находитесь на странице: 1из 14

Chapter3/KMEM3211/sj/2012

Chapter 3: Harmonic Response with a Single Degree of Freedom

 When a vibratory system has an external force acting on it, such as from a gust of wind,
an unbalanced motor, or road surface variation, its response depends not only on the initial
conditions but also on the nature of the external force, called forcing function or forced
response.
 Harmonic response – the response of a system to either a sinusoidal or cosinusoidal
forcing function

3.1 Response of an undamped system under harmonic force

The equation of motion of a mass-spring system:

m x́ +kx =f (t) (3.1)

If a force f ( t )=F 0 cos ωt acts on the mass m of an undamped system, the equation of
motion is
m x́ +kx =F 0 cos ωt (3.2)

The solution for the displacement x (t) consists of two parts: the homogenous
(complimentary) solution, and the particular solution. The homogenous solution for the
problem is given by the free vibration discussion, given as

x h ( t )=C 1 cos ωn t+C 2 sin ωn t (3.3)

The particular solution depends on the nature of the forcing function. Because the exciting
force f ( t ) is harmonic, the particular solution is also harmonic and has the same frequency
ω , with the solution as
x p ( t )= A cos ωt (3.4)

By substituting equ. (3.4) into equ. (3.2),

F0 δ st
A= 2
= 2
k −m ω ω (3.5)
1−
( )
ωn

where δ st =F 0 /k denotes the deflection of the mass under a force F0 and is sometimes
called static deflection because F0 is a constant (static) force. Thus, the total solution of
equ. (3.2) becomes
x ( t )=x h ( t ) + x p ( t )
F0
x ( t )=C 1 cos ωn t+C 2 sin ωn t+ cos ωt (3.6)
k −mω 2

Using initial conditions t =0 , x ( 0 )=x 0 , x́ ( 0 )=x́ 0 ,

F0 x́ 0
C1 =x0 − 2 , C2 =
k−m ω ωn

1
Chapter3/KMEM3211/sj/2012

Equ. (3.6) becomes

F0 x́ 0 F0
(
x ( t ) = x 0−
k−mω 2 ) cos ωn t+
ωn ( )
sin ω n t +
k−mω 2
cos ωt (3.7)

The magnification factor can be expressed as

A 1
=
δ st ω
2
(3.8)
1−
( )
ωn

The variation of the magnification factor with the frequency ratio r=ω/ω n is shown
below.

From this figure, the response of the system can be identified in three cases:
1. When 0<ω /ω n <1, the response is given in equ. (3.4) without change. The
harmonic response of the system x p ( t ) is said to be in phase with the external force
as shown below:

2
Chapter3/KMEM3211/sj/2012

2. When ω /ωn >1, the harmonic response of the system x p ( t ) is in negative value
where the amplitude of motion A is redefined to be a positive quantity, as shown
below:

3. When ω / ωn=¿ 1, the amplitude of the harmonic response of the system x p ( t )


becomes infinite. This condition is called resonance with the equ. (3.7) becomes
4.
x́ δ ω t
( )
x ( t )=x 0 cos ω n t + 0 sin ωn t+ st n sin ωn t
ωn 2
(3.9)

3
Chapter3/KMEM3211/sj/2012

3.2 Response of a damped system under harmonic force

The equation of motion of a mass-spring-damper system:

m x́ +c x́+ kx=f (t) (3.10)

When the forcing function f ( t )=F 0 sin ωt , equ. (3.10) becomes

m x́ +c x́+ kx=F 0 sin ωt (3.11)

1. Free response
For m s2 + cs+k =0 , the solution for the roots will be one of the following cases:
i. Two distinct, real roots, denoted r 1 and r 2 . This case will occur if
r t r t
c 2−4 mk> 0 with the free response form is A 1 e + A 2 e . 1 2

ii. Two equal (repeated) root, denoted r 1 and r 1 . This case will occur if
2
c −4 mk=0 . These roots will be real. For this case the free response form is
r t r t
A 1 e +t A2 e .
1 1

iii. Two complex conjugate roots, denoted r +iq and r−iq , where

q= √
r=
−c 4 mk−c 2
2m 2m
2
This case will occur if c −4 mk< 0 . For this case the free response form is
B ert sin ⁡( qt+ ψ) .

2. Sine response with complex roots


To obtain the complete solution, use

x ( t )=¿ Free response form +¿ Forcing function form + Forcing function derivative
form

The solution then become

4
Chapter3/KMEM3211/sj/2012

rt rt
x ( t )= A e sin qt+ B e cos qt+ C sin ωt + D cos ωt (3.12)
With

x́=( rA−Bq ) e rt sin qt + ( qA +Br ) e rt cos qt+ Cωcos ωt−Dω sin ωt (3.13)
2 2 rt 2 2 rt
x́=( r A−q A−2 rqB ) e sin qt + ( r B−q B+2 rqA ) e cos qt
2 2
−C ω cos ωt−D ω cos ωt (3.14)

The solution for A , B , C , and D are

−ω F 0 rc+ k−mω 2
A= (3.15)
q ( k−mω 2) +(cω)2
cω F 0
B= 2 (3.16)
( k −mω 2 ) +(cω )2
(k−mω 2) F0
C= 2 (3.17)
( k−mω 2) +(cω)2
−cω F 0
D=−B= 2 (3.18)
( k −m ω2 ) +(cω)2

Thus, the sinusoidal forcing function F0 sin ωt , the forced response which is the total
response for zero initial conditions is

F0
) [ ]
−ω (
x ( t )= rc+ k−mω 2) ert sin qt+ cω e rt cos qt
2 2 2 q
( k −m ω ) + ( cω
+F0
2 2 2
[ ( k−mω 2) sin ωt −cω cos ωt ] (3.19)
( k−mω ) + ( cω )

3. Steady-state response
The steady-state response is that part of the response which does not disappear as time
goes on. The transient response is that part of the response which disappears, as shown
below.

5
Chapter3/KMEM3211/sj/2012

For equ. (3.10), the transient response consists of the terms containing e rt if r <0 .
The steady-state response consists of the sin ωt and cos ωt terms. The steady-state
response is

F0
x ( t )=¿ 2 2 2
[ ( k−mω 2) sin ωt −cω cos ωt ] (3.20)
( k−mω ) + ( cω )

Equ. (3.11) can be written as a single sine function:

x ( t )= X sin ⁡[ ωt +ϕ ( ω ) ] (3.21)
where
F0
X= (3.22)
√ ( k −m ω ) +(cω)
2 2


ϕ=tan−1
( mω2 −k ) (3.23)

The magnification factor can be expressed as

X 1 1
= =
δ st 1/ 2
√( 1−r ) + ( 2 ζr )
2 2

{[ ]}
2 2 2

( )] [
2
ω ω (3.24)
1− + 2ζ
ωn ωn
and

6
Chapter3/KMEM3211/sj/2012

( ( ))

ωn 2 ζr
ϕ=tan−1
1−
ω 2
=tan−1
( 1−r 2 ) (3.25)
ωn

The variation of the magnification factor with the frequency ratio r=ω/ω n is shown
below.

The following characteristics can be noted:


1. For an undamped system, M → ∞ as r →1 .
2. Any amount of damping reduces M for all values of the forcing frequency.
3. For any specified value of r , a higher value of damping reduced the value of M
.
4. In the degenerate case of a constant force, the value of M =1 .
5. The reduction in M in the presence of damping is very significant at or near
resonance.
6. The amplitude of forced vibration becomes smaller with increasing values of the
forcing frequency.
7. For 0<ζ < 1/ √ 2 , the maximum value of M occurs when

r= √ 1−2ζ 2 or ω=ω n √ 1−2 ζ 2 (3.26)

which can be seen to be lower than the undamped natural frequency ωn and the
damped natural frequency
ω d=ωn √ 1−2 ζ 2 (3.27)
8. The maximum value of X is given by

X 1
( )
δ st max
=
2ζ √ 1−2 ζ 2
(3.28)

7
Chapter3/KMEM3211/sj/2012

and the value of X at ω=ω n by

X 1
( )
δ st ω=ω n
=

(3.29)

1 dM 1
9. For ¿ , =0 when r=0 . For ζ > , the graph of M
√2 dr √2
monotonically decreases with increasing values of r .

4. Total response
For an underdamped system, the complete solution is

x ( t )=x h ( t ) + x p ( t )
−ζ ω n t
x ( t )= X 0 e cos ( ωd t−ϕ 0 ) + X cos (ωt−ϕ) (3.30)

X and ϕ are given by equ. (3.24) and (3.25), respectively, and X 0 and ϕ 0 can
be determined from the initial conditions. For the initial conditions t =0 , x ( 0 )=x 0 ,
x́ ( 0 )=x́ 0 ,
x 0=X 0 cos ϕ0 + X cos ϕ (3.31)
x́ 0=−ζ ωn X 0 cos ϕ0 +ω d X 0 sin ϕ 0+ ωX sin ϕ (3.32)

The solution of equ. (3.31) and (3.32) gives


1/ 2

[
X 0 = ( x 0−X cos ϕ ) 2+
1
ωd 2(
ζ ωn x 0+ x́ 0 −ζ ωn X cos ϕ−ωX sin ϕ ) 2
] (3.33)

ζ ω n x 0 + x́ 0−ζ ω n X cos ϕ−ωX sin ϕ


tan ϕ 0= (3.34)
ω d ( x0 −X cos ϕ )

3.3 Response of a damped system under f ( t )=F 0 eiωt

With f ( t )=F 0 eiωt , equ. (3.10) becomes

iωt
m x́ +c x́+ kx=F 0 e (3.34)

The actual excitation is given only by the real part of f ( t ) and the response will also be
given only by the real part of x ( t ) . By assuming the particular solution x p ( t ) as

iωt
x p ( t )= X e (3.35)

By substituting equ. (3.35) into (3.34)

F0
X= (3.36)
( k−m ω2 ) +icω
Can also be expressed as

8
Chapter3/KMEM3211/sj/2012

F0
X= 1/ 2
e−iϕ (3.37)
[ ( k−mω ) + c ω ]
2 2 2 2

where

ϕ=tan−1
( k−m ω2 ) (3.38)

The steady-state solution is

F0
x p ( t )= 1 /2
ei (ωt −ϕ) (3.39)
[ ( k−m ω ) +c
2 2 2
ω2 ]

In a complex frequency response, H (iω) , of the system, equ. (3.36) can be rewritten as

kX 1
= ≡ H (iω) (3.40)
F 0 1−r 2 +i2 ζr

The absolute value of H (iω) is given by

|H ( iω )|= kX
F | |0
=
[ ( 1−r ) +( 2 ζr ) ]
2 2
1
2
1/ 2 (3.40)

Recalling that e iϕ=cos ϕ +isin ϕ , equ. (3.40) and (3.40) are related

H (iω ) =|H ( iω)|e−iϕ (3.41)

where ϕ can be expressed as


2 ζr
ϕ=tan−1
( 1−r ) 2 (3.41)

Equ. (3.39) can be expressed as

F0 i(ωt−ϕ )
x p ( t )= |H (iω )|e (3.42)
k

If f ( t )=F 0 cos ωt , the corresponding steady-state solution is given by the real part of equ.
(3.39),
F0
x p ( t )= 1
cos ( ωt−ϕ )
[ ( k−m ω ) +c 2 2 2
ω2 ]
2

¿ℜ [ F0
k
F
] [
H ( iω ) eiωt =ℜ 0 | H ( iω )|e i(ωt−ϕ )
k ] (3.43)

If f ( t )=F 0 sin ωt , the corresponding steady-state solution is given by the imaginary part of
equ. (3.39),

9
Chapter3/KMEM3211/sj/2012

F0
x p ( t )= 1
sin ( ωt −ϕ )
[ ( k−m ω ) +c
2 2 2 2 2
ω ]
¿ℑ [ F0
k
|H ( iω)|e i(ωt −ϕ) ] (3.44)

3.4 Response of a damped system under the harmonic motion of the base

As shown below, sometimes the base or support of a spring-mass-damper system undergoes


harmonic motion.

Let y (t) denote the displacement of the base and x (t) the displacement of the mass
from its static equilibrium position at time t .

Net elongation of the spring: x− y


Relative velocity between two ends of damper: x́− ý
Equation of motion: m x́ +c ( x́− ý ) +k ( x− y )=0 (3.45)

If y ( t )=Y sin ωt , equ. (3.45) becomes

m x́ +c x́+ kx=ky + c ý=kY sin ωt+ cωY cos ωt


¿ A sin(ωt −α ) (3.46)

This shows that giving excitation to the base is equivalent to applying a harmonic force of
magnitude A to the mass. By using the solution indicated by equ. (3.44), the steady-state
response of the mass, x p (t) , can be expressed as

Y √ k 2+(cω)2
x p ( t )= 1 /2
sin ⁡( ωt −ϕ 1−α ) (3.47)
[(k−m ω2 )2+(cω )2 ]

where ϕ 1=tan
−1
( k −mcωω )2 . Using trigonometric identities, equ. (3.47) can be rewritten as

x p ( t )= X sin (ωt−ϕ) (3.48)


10
Chapter3/KMEM3211/sj/2012

where
1/ 2 1/ 2
X
Y
=
[ k 2 +(cω)2
(k −m ω2 )2+(cω)2 ] [ =
1+(2 ζr)2
(1−r 2 )2+(2 ζr)2 ] (3.48)

ϕ=tan−1
[ mc ω3
k ( k −m ω2 ) +(ωc)2 ] [
=tan −1 2 ζ r3
1+(4 ζ 2−1) r 2 ] (3.49)

The ratio of the amplitude of the response x p ( t ) to that of the base motion y ( t ) ,
X / Y , is called the displacement transmissibility. If the harmonic excitation of the base is
expressed in complex form as y ( t )=ℜ(Y e iωt ) , the response of the system can be
expressed as

x p ( t )=ℜ ({ 1−r1+i2+ i2ζrζr )Y e }


2
iωt
(3.50)

and the displacement transmissibility as

X 2 1/ 2
=T d=[ 1+(2 ζr) ] |H (iω)| (3.51)
Y

X
where |H (iω)| is given by equ. (3.40). The variation of ≡T d and ϕ given by
Y
equ. (3.48) and (3.49) are shown below for different values of r and ζ .

Noted that
1. The value of T d is unity at r=0 and close to unity for small values of r .
2. For an undamped system, T d → ∞ at resonance ( r=1 ).
3. The value of T d is less than unity ( T d <1 ) for values of r > √ 2 (for any
amount of damping ζ ).
4. The value of T d is unity for all values of ζ at r= √2 .
5. For r < √ 2 , smaller damping ratios lead to larger values of T d . On the other
hand, for ¿ √ 2 , smaller values of damping ratio lead to smaller values of Td .

11
Chapter3/KMEM3211/sj/2012

6. The displacement transmissibility, T d , attains a maximum for 0<ζ < 1 at the


frequency ratio r=r m <1 given by

1 1/ 2
r m=

[ √ 1+8 ζ 2−1 ] (3.52)

1. Force transmitted
In figure below, a force F is transmitted to the base or support due to the reactions from
the spring and the dashpot.

This force can be determined as

F=k ( x− y ) +c ( x́− ý )=−m x́ (3.53)

From equ. (3.48), equ. (3.53) can be written as

F=mω 2 X sin ( ωt−ϕ )=F T sin ⁡( ωt−ϕ) (3.54)

where FT is the amplitude or maximum value of the force transmitted to the base given
by
1 /2
FT 2
kY
=r
[ 1+(2 ζr)2
2
( 1−r 2 ) +(2ζr )2 ] (3.55)

The ratio (FT /kY ) is known as the force transmissibility. The variation of the force
transmitted to the base with the frequency ratio r is shown below for different values
of ζ .

12
Chapter3/KMEM3211/sj/2012

2. Relative motion
If z=x− y denotes the motion of the mass relative to the base, the equation of motion,
equ. (3.45), can be rewritten as
2
m ź +c ź+ kz=−m ý =mω Y sin ωt (3.56)

The steady-state solution of equ. (3.56) is given by

mω2 Y sin(ωt −ϕ1 )


z ( t )= 1 /2
=Z sin (ωt−ϕ1) (3.57)
[(k−mω2 )2+(cω)2 ]
where Z , the amplitude of z ( t ) , can be expressed as
2 2
mω Y r
Z= =Y (3.58)
√( k−mω2)2 +(cω)2 2

( 1−r 2 ) +(2ζr )2

and ϕ 1 by
ϕ 1=tan −1
( k −mcωω )=tan ( 1−r
2
2 ζr
)
−1
2 (3.59)

The ratio Z / Y is shown below.

13
Chapter3/KMEM3211/sj/2012

14